Comparison of Quality of Life During Hormonal Therapy and Chemotherapy in Breast Cancer Patients at Dr. Moewardi Hospital: A Cross-Sectional Study - Pigur Agus Marwanto; Widyanti Soewoto (Health and Medical Journal, 2026)
Introduction: Breast cancer is the most frequently diagnosed cancer and the leading cause of cancer-related death among women worldwide, accounting for 25% of all cancer cases and 15% of cancer-related mortality in women. Adjuvant therapies include chemotherapy, hormonal therapy, targeted therapy, radiation, or combinations thereof. The quality of life (QoL) of breast cancer patients varies depending on type of therapy, patient’s condition, and associated side effects. Evaluating QoL differences between hormonal therapy and chemotherapy is essential to assess treatment outcomes and guide clinical decisions. Methods: This cross-sectional study involved 240 breast cancer survivors treated at the Oncology Department of Dr. Moewardi Hospital. Selected participants using random sampling in two groups:  120 patients each groups undergoing chemotherapy and hormonal therapy. Data were collected through interviews and standardized questionnaires using the EORTC QLQ-C30 instrument. QoL data were categorized, and statistical analysis was performed using chi-square tests to examine associations between treatment type and QoL. Logistic regression was used to assess the strength of relationships between variables. Results: Groups receiving hormonal therapy, 116 (96.7%) reported good QoL, and 4 (3.3%) reported moderate QoL. In the chemotherapy group, 80 (66.7%) reported good QoL, 39 (32.5%) moderate, and 1 (0.8%) poor QoL. A statistically significant difference in QoL was observed between the two groups (p = 0.001). Dyspnoea was the only symptom that showed a significant association with treatment type (r = 0.208; p = 0.020). Across general health status, functional scales, and symptom scales, hormonal therapy was associated with better QoL outcomes than chemotherapy. Conclusion: There is a significant difference in the QoL of breast cancer patients undergoing hormonal therapy compared to chemotherapy. Hormonal therapy was a better overall QoL.